Ab initio dynamical mean field theory with natural orbitals renormalization group impurity solver - Jia-Ming Wang; Jing-Xuan Wang; Rong-Qiang He; Li Huang; Zhong-Yi Lu (npj Computational Materials)
Abstract In this study, we introduce a novel implementation of density functional theory integrated with single-site dynamical mean-field theory to investigate the complex properties of strongly correlated materials. This ab initio many-body computational toolkit, termed Zen, utilizes the VASP and Quantum ESPRESSO codes to perform first-principles calculations and generate band structures for realistic materials. The challenges associated with correlated electron systems are addressed through two distinct yet complementary quantum impurity solvers: the natural orbitals renormalization group solver for zero temperature and the hybridization expansion continuous-time quantum Monte Carlo solver for finite temperatures. To validate the performance of this toolkit, we examine three representative cases: correlated metal SrVO3, unconventional superconductor La3Ni2O7, and Mott insulator MnO. The calculated results exhibit excellent agreement with previously available experimental and theoretical findings. Thus, it is suggested that the Zen toolkit is proficient in accurately describing the electronic structures of d-electron correlated materials.